Location and stoichiometry of the protease CspB and the cortex-lytic enzyme SleC in Clostridium perfringens spores. (September 2015) - Banawas, Saeed; Korza, George; Paredes-Sabja, Daniel; Li, Yunfeng; Hao, Bing; Setlow, Peter; Sarker, Mahfuzur R.
Abstract: The protease CspB and the cortex-lytic enzyme SleC are essential for peptoglycan cortex hydrolysis during germination of spores of the Clostridium perfringens food poisoning isolate SM101. In this study, Western blot analyses were used to demonstrate that CspB and SleC are present exclusively in the C. perfringens SM101 spore coat layer fraction and absent in the lysate from decoated spores and from the purified inner spore membrane. These results indicate why decoating treatments greatly reduce both germination and apparent viability of C. perfringens spores in the absence of an exogenous lytic enzyme. In addition, quantitative Western blot analyses showed that there are approximately 2000 and 130, 000 molecules of CspB and pro-SleC, respectively, per C. perfringens SM101 spore, consistent with CspB's role in acting catalytically on pro-SleC to convert this zymogen to the active enzyme. Highlights: CspB and SleC are detected in coat layer fraction of Clostridium perfringens SM101 spore. CspB and SleC are absent in lysates from decoated spores and inner spore membrane. Levels of CspB and SleC are ∼2000 and 13, 000 molecules/spore, respectively.